Pharmacological and Phytochemical Screenings of Ethanol Extract of Etlingera linguiformis (Roxb.) R.M.Sm. Growing in Bangladesh (Bangladesh Pharmaceutical Journal, 2013)
The present study was conducted to investigate the bio-activities of ethanol extract of Etlingera linguiformis (Roxb.) R.M.Sm. as well as to determine the chemical profiles of the extract. The antibacterial and antifungal activities of the crude extract were evaluated by the disc diffusion method against 4 Gram positive and 7 Gram negative pathogenic bacteria and 7 fungi using Ciprofloxacin and Fluconazole as standards, respectively. The minimum inhibitory concentration (MIC) was determined by the serial dilution method. The anti-atherothrombosis activity was assessed by using Streptokinase (SK) as standard. Moreover, the in-vitro anti-inflammatory and membrane stablization tests were performed. In the anti-bacterial and antifungal activity test, the zones of inhibition were found within the range of 10.0-15.0 and 10.0-22.0 mm, respectively. The highest zone of inhibition was obtained against Bacillus cereus (15.0 mm) and Blastomyces dermatitidis (22.0 mm). In the minimum inhibitory concentration (MIC) test the crude extract inhibited the growth of Blastomyces dermatitidis significantly at 31.2 ?g/ml. In the anti-atherothrombosis activity test, the extract revealed moderate clot lysis by 15.15%. Moreover, the extract produced inhibition of protein denaturation and haemolysis by 34% and 38.98% in the in vitro antiinflammatory and membrane stablization tests. Preliminary phytochemical screenings of the crude extractives demonstrated the presence of alkaloids, steroids, tannins, reducing sugars and gums. The extract also exhibited good biological activities. Therefore, the plant should be subjected to systematic bioactivity guided isolation in order to obtain the active molecules. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14488 Bangladesh Pharmaceutical Journal 16(1): 33-37, 2013